REACTIVE CARBONYL SPECIES AND THEIR ROLES IN SARCOPLASMIC RETICULUM Ca(2+) CYCLING DEFECT IN THE DIABETIC HEART - Tian, Chengju (Heart Fail Rev, 2014)
Efficient and rhythmic cardiac contractions depend critically on the adequate and synchronized release of Ca(2+) from the sarcoplasmic reticulum (SR) via ryanodine receptor Ca(2+) release channels (RyR2) and its reuptake via sarco(endo)plasmic reticulum Ca(2+)-ATPase (SERCA2a). It is well established that this orchestrated process becomes compromised in diabetes. What remain incompletely defined are the molecular mechanisms responsible for the dysregulation of RyR2 and SERCA2a in diabetes. Earlier, found elevated levels of carbonyl adducts on RyR2 and SERCA2a isolated from hearts of type 1 diabetic rats and showed the presence of these post-translational modifications compromised their functions. We also showed that these mono- and di-carbonyl reactive carbonyl species (RCS) do not indiscriminately react with all basic amino acid residues on RyR2 and SERCA2a; some residues are more susceptible to carbonylation (modification by RCS) than others. A key unresolved question in the field is which of the many RCS that are upregulated in the heart in diabetes chemically react with RyR2 and SERCA2a? This brief review introduces readers to the field of RCS and their roles in perturbing SR Ca(2+) cycling in diabetes. It also provides new experimental evidence that not all RCS that are upregulated in the heart in diabetes chemically react with RyR2 and SERCA2a, methylglyoxal and glyoxal preferentially do.